Cross-cultural adaptation and reliability of the European Portuguese version of the Musculoskeletal Health Questionnaire: A methodological study. - Hermínia Ribeiro; Eduardo Brazete Cruz; Ana Castro; Ana Rodrigues; Bruno Heleno; Teresa L Dias; Diogo Pires; Diogo Pires (PLoS ONE)
Purpose To culturally adapt the Musculoskeletal Health Questionnaire (MSK-HQ) to European Portuguese and evaluate its reliability in individuals with musculoskeletal conditions. Materials and methods The study was carried out in two phases. In the first phase, the MSK-HQ was translated and culturally adapted. In the second phase, a longitudinal observational study was carried out with a convenience sample of participants with musculoskeletal conditions. Data collection began at the start of physiotherapy treatments by filling in the MSK-HQ and Numeric Pain Rating Scale (NPRS). After 4-7 days, the participants were asked to fill out the MSK-HQ once again, as well as the Patient Global Improvement Change (PGIC) scale. The data collected was used to study internal consistency, test-retest reliability, and measurement error. Floor and ceiling effects were also analysed. Results The MSK-HQ was successfully translated and adapted into European Portuguese. The second phase of the study had a sample of 191 participants. This study demonstrated high internal consistency (Cronbach's α = 0.885) and excellent test-retest reliability (ICC(2,1) = 0.908). The analysis of measurement error resulted in an SEM of 2.818 and an SDC at 7.811. No floor or ceiling effect was observed. Conclusions The MSK-HQ-PT is a reliable instrument for measuring musculoskeletal health. Further studies on its validity and responsiveness are needed.